Critical Chinese as an Additional Language education in Australia: A journey to voices, courage and hope. (22nd June 2021) - Xu, Wen; Knijnik, Jorge
Abstract : This article addresses key topics of Chinese as an Additional Language (CAL) education and classroom pedagogical practices. It reports on a 3‐year ethnographic study within Australian schools to discuss dialogic pedagogical practices and students' aspirations. Based on Freire's conceptualisation of conscientização and banking education, the purpose of this article is therefore to unpack a journey to voices, courage and hope of a cohort of socially, linguistically and economically disadvantaged students in Western Sydney, one of the most culturally diverse regions in the country. Their experiences, responses, dreams and understanding of CAL education in multicultural Australia were thus captured. Our data shows that critical CAL education might point to some avenues for the educational equity agenda. By arguing that emancipatory and critical practices could enhance students to achieve consciousness and collective self‐transformation, we aim to make a contribution to the literature on CAL and languages education, which all too often isolates from broader issues in educational theory. The article also adds to the limited research that engages with CAL classroom data. Our critical approach to CAL education illuminates the intersections between language and social inclusion. Considering the worldwide growing upheaval and scepticism around CAL education, we call for writing inclusive languages education and related pedagogical practices into the social inclusion agenda in Australia and internationally, for the teaching and learning of all additional languages.